Conferring rights on citizens - Laws and their implementation - Dubhashi, P.R. (2014)
When a government chooses to neglect growth to launch populist welfare schemes it faces the hazard of half-hearted implementation because of inadequate resources and resultant low sustainability. The last one decade witnessed a slew of measures to bestow a number of rights on citizens which are already obligatory on the state by virtue of directive principles enshrined in the Constitution. But the initiatives too often suffered from faulty conception or slow and ham-fisted implementation Several such measures have failed to make the desired impact because of prevailing ground realities, desultory attitude of the state governments and overall wider economic factors. Putting 'rights' on statute book will not be effective unless appropriate implementation strategy is in place. - Reproduced.
Keywords: Civil and political rights